A bi‐level mobile energy storage pre‐positioning method for distribution network coupled with transportation network against typhoon disaster - Ke Zhou; Qingren Jin; Bin Feng; Lifang Wu (IET Renewable Power Generation)
Abstract Mobile energy storage (MES), as a flexible resource, plays a significant role in disaster emergency response. Rational pre‐positioning ahead of disasters can accelerate the dispatch of MES to power outage areas, and further reduce load losses. This paper focuses on typhoon disasters and studies the MES pre‐positioning method for distribution networks coupled with transportation networks. Firstly, a typhoon model considering the typhoon eye was formulated. Secondly, the analysis covering the diverse impacts of typhoons on the ‘generation‐transmission‐load‐road’ system was conducted. Subsequently, a bi‐level pre‐positioning model, considering multi‐index evaluation, was established based on scenario‐based stochastic optimization. Finally, the modified MATPOWER 18‐node test system was utilized to verify the performance of the proposed method, and the simulation results demonstrated its effectiveness and applicability.